PENERAPAN TEKNIK MIND MAPPING DALAM STRATEGI QUANTUM LEARNING UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR BIOLOGI SISWA KELAS XI IPA2 SMA NURUL FALAH PEKANBARU TA. 2009/2010 - Yustina '; Rosmaini S; Yessi Wulandari (Program Studi Pendidikan Biologi, 2011)
Classroom Action Research has been carried out (PTK), which aims to enhance motivation and learning outcomes Biological science using Mind Mapping Strategies in Quantum Learning in class XI Science 2 Nurul Falah Pekanbaru SMA FY 2009/2010. The study was conducted on May 21, 2010 until the date of June 7, 2010. number of students in research as many as 40 people (12 male students and 28 female students). The parameters of this study is the motivation and learning outcomes. The results showed that the average score of the students' motivation before learning to use Mind Mapping Strategies in Quantum Learning is 2.12 (Medium), and the average score of motivation after learning to use Mind Mapping Strategies in Quantum Learning is 3.01 (High) , with a percentage (%) increased motivation for 42.01%. The average absorption cycle 1 students 77.8% (good), while in cycle 2 the average student absorption of 84.4% (very good). Mastery learning of individual students in cycle 1 (daily tests I) that is 90% (complete), at cycle 2 mastery learning students increased to 100% (complete). The final conclusion of Learning Implementation Using Mind Mapping Strategies in Quantum Learning to Enhance Motivation and Learning Outcomes High School Students Science Biology Pekanbaru Nurul Falah School Year 2009/2010.